Workshop on Comparative analysis of k populations with Non Parametric for Research in Social Sciences and Education - Rosita Kusumawati; Dhoriva Urwatul Wutsqa; Kismiantini Kismiantini; Syarifah Inayati; Muhammad Fauzan; Ezra Putranda Setiawan; Bayutama Isnaini (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2022)
Data obtained from social science and education research is often in the form of categorical data, namely nominal or ordinal. This makes the parametric approach less appropriate for use in some social science and education data. One solution is to use a nonparametric approach. This underlies the holding of community service activities in a workshop on comparison analysis of k population with a nonparametric approach for social science research and education. Participants in this workshop consisted of academics and practitioners, and students from various study programs in Indonesia. The workshop was carried out by providing material and demonstrating using R software as an analytical tool, which was held online for two days. On the first day, the material presented was a nonparametric approach to the comparison of k independent populations along with a demonstration of using R software, while for k dependent populations along with a demonstration of using R software was given on the second day. Participants were given data on social sciences and education in providing materials and demos of the R software. Based on the results of questionnaires, observations, and questions and answers, participants seemed enthusiastic in participating in the R software's material and demo sessions. In addition, participants can perform various tests in a nonparametric approach for k independent and dependent populations using the R software. Participants can also provide an accurate interpretation of the output of the R software.